The Preventing Effects of Lisinopril, Sildenafil and Combined Usage of Them on the Formation of Intra-Abdominal Adhesion - Kırkıl, Cüneyt; Coşkun, Serdar; Bülbüller, Nurullah; Aygen, Erhan; Karabulut, Koray (Fırat University, 2011)
Objective: In this study, it was aimed to compare the effectiveness of lisinopril and sildenafil on the prevention of intra-abdominal adhesions and to investigate whether there was a synergistic effect if they were combined. Materials and Methods: Fourty rats divided into four groups and mesothelial damage created. No medication was given to rats in group 1, lisinopril (6.5 mg/kg/d) in group 2, sildenafil (0.8 mg/kg/d) in group 3, and lisinopril combined with sildenafil in group 4 were given to rats by gavage for 7 days. Then, abdominal cavities were reopened and adhesion scores were determined. Results: The mean intra-abdominal adhesion scores of groups were 2.3±0.5, 0.9±0.7, 0.6±0.8, and 0.7±0.9, respectively. The mean adhesion scores of all treatment groups were significantly lower than control group (p0.05,and group 3 vs group 4 p>0.5). Conclusion: : Lisinopril and sildenafil alone is effective in preventing the formation of intra-abdominal adhesions. Their combination does not increase their potencies.

Amaç: Bu çalışmada lisinopril ve sildenafilin karın içi yapışıklıkları önlemedeki etkinliklerinin karşılaştırılması ve birlikte uygulanmaları halinde sinerjik etki gösterip göstermeyeceklerinin incelenmesi amaçlanmıştır. Gereç ve Yöntem: Kırk adet rat 4 gruba ayrılıp mezotel hasarı oluşturuldu. Birinci gruptaki ratlara her hangi bir ilaç verilmez iken 2. gruptakilere lisinopril (6.5 mg/kg/gün), 3. gruptakilere sildenafil (0.8 mg/kg/gün) ve 4. gruptakilere hem lisinopril hem de sildenafil gavaj yoluyla 7 gün verildi. Sonra karın boşluğu tekrar açılıp yapışıklık skorları belirlendi. Bulgular: Grupların ortalama karın içi yapışıklık skorları sırasıyla 2.3±0.5, 0.9±0.7, 0.6±0.8 ve 0.7±0.9 idi. Tüm tedavi gruplarının yapışıklık skorları kontrol grubununkinden belirgin olarak daha düşüktü (p0.05, grup 3 vs grup 4 p>0.5). Sonuç: Lisinopril ve sildenafil tek başlarına karın içi yapışıklık gelişmesini önlemede etkilidir. Birlikte kullanımları onların güçlerini artırmaz.
Lisinopril, Sildenafil ve Birlikte Kullanımlarının Karın İçi Yapışıklık Oluşmasını Önleyici Etkileri